Determinants of Post - partum contraception practices in urban slums of central Karnataka, India - B, Shubha Davalagi; Revanna, Rashmi; Agadi, Nagarajachari (Indian Journal of Community Health, 2016)
Background: The largest proportion of women with an unmet need for contraception is found among those in their first year after childbirth; concentrating efforts to reduce unmet need among these women could have additionally bigger impact on increasing contraceptive use than concentrating on any other group. Aims & Objectives: To know the knowledge & practices of post – partum contraception among mothers in urban slums. Material & Methods: Cross sectional study conducted in urban slums for duration of six months. Study population included mothers in extended post – partum period residing in urban slums. Mothers were interviewed using pre – tested, semi – structured questionnaire. Data was analyzed using SPSS v 22.0 and, chi square test and logistic regression analysis was employed. P value of <0.05 was considered statistically significant. Results: Majority of the mothers in our study were in the age group of 20-24 years (46%). Mean age was 21.6 ± 3.1years. Majority of the mothers (56%) were Hindus. Mean age of marriage observed was 18.2±2.1years. In the present study, majority (76%) had knowledge of post – partum contraceptive methods, but only 17% of the mothers were using contraception. Unmet need for post – partum contraception was found among 49% of mothers. Conclusions: Inspite of being aware, the practice of family planning was very low among post-partum mothers. The study highlights the impact of socio cultural factors like religion, caste, number of living children, duration of marriage and ANC service utilization on post – partum contraception usage among mothers.